Minimal residual disease in lymph nodes after achievement of complete remission predicts time to relapse in dogs with large B‐cell lymphoma. (4th February 2019) - Chalfon, Carmit; Martini, Valeria; Comazzi, Stefano; Aresu, Luca; Stefanello, Damiano; Riondato, Fulvio; Ferrari, Roberta; Marconato, Laura
Abstract : Most dogs with large B‐cell lymphoma (LBCL) that undergo chemotherapy and achieve clinical complete remission (CR) eventually relapse. However, time to relapse (TTR) is unpredictable. The aims of this prospective study were to assess the influence of post‐chemotherapy lymph node (LN) infiltration by large CD21+ cells using flow cytometry (FC) on TTR, and to establish a cut‐off value of prognostic significance. Dogs with newly‐diagnosed, completely staged LBCL in CR after treatment were enrolled. Minimal residual disease (MRD) analysis by FC was performed on LN aspirates. TTR was calculated between MRD and relapse. Thirty‐one dogs were enrolled: 4% had stage V disease, and diffuse large B‐cell lymphoma was the most common histotype (74%). Based on LN infiltration at MRD evaluation, three groups were created: (a) acellular samples, (b) ≤0.5% infiltration and (c) >0.5% infiltration. Overall median TTR was 154 days (range, 31‐1974): 22 (71%) dogs relapsed during the study period, whereas 9 (29%) dogs did not. The difference among the three groups was significant ( P = 0.042 log‐rank test): median TTR was not reached for dogs with LN infiltration ≤0.5% (range, 195‐429 days), 164 days (range 63‐1974) for dogs with acellular LN samples, and 118 days (range, 31‐232) for dogs with LN infiltration >0.5%. These results demonstrate that MRD assessment by FC on LN aspirates in dogs with LBCL in clinical CR predicts TTR. LN infiltration by >0.5% large CD21+ cells after treatment is an unfavourable prognostic factor.